2010
DOI: 10.1523/jneurosci.1541-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

The R109H Variant of Fascin-2, a Developmentally Regulated Actin Crosslinker in Hair-Cell Stereocilia, Underlies Early-Onset Hearing Loss of DBA/2J Mice

Abstract: The quantitative trait locus ahl8 is a key contributor to the early-onset, age-related hearing loss of DBA/2J mice. A nonsynonymous nucleotide substitution in the mouse fascin-2 gene (Fscn2) is responsible for this phenotype, confirmed by wild-type BAC transgene rescue of hearing loss in DBA/2J mice. In chickens and mice, FSCN2 protein is abundant in hair-cell stereocilia, the actin-rich structures comprising the mechanically sensitive hair bundle, and is concentrated toward stereocilia tips of the bundle's lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
167
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(177 citation statements)
references
References 44 publications
9
167
1
Order By: Relevance
“…A point mutation in Drosophila fascin (the singed mutant) in Gly 409 (to Glu) (equivalent to Gly 393 in human fascin 1, next to the critical His 392 in actin-binding site 1) reduced fascin activity in vivo, implying that this actin-binding site 1 is functionally critical (40). Furthermore, a point mutation of Arg 109 to His in fascin-2 (corresponding to Arg 110 in fascin-1 in the actinbinding site 2) led to early-onset hearing loss in mice (fascin-2 is the main actin-bundling protein in hair-cell stereocilia) (41). Also, fascin(K22E/K43E/R398E) and fascin(R271E/K353E/ K358E) mutants had been shown to be defective in actin bundling (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A point mutation in Drosophila fascin (the singed mutant) in Gly 409 (to Glu) (equivalent to Gly 393 in human fascin 1, next to the critical His 392 in actin-binding site 1) reduced fascin activity in vivo, implying that this actin-binding site 1 is functionally critical (40). Furthermore, a point mutation of Arg 109 to His in fascin-2 (corresponding to Arg 110 in fascin-1 in the actinbinding site 2) led to early-onset hearing loss in mice (fascin-2 is the main actin-bundling protein in hair-cell stereocilia) (41). Also, fascin(K22E/K43E/R398E) and fascin(R271E/K353E/ K358E) mutants had been shown to be defective in actin bundling (24).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the above conformational changes in ␤-trefoil fold 2, these individual mutations had effects on their local environment. In fascin(S39D), the introduction of a negative charged residue changed the orientation of the side chain of the positively charged residue Lys 41 , which is critical for actin bundling (Fig. 5, A-C, and Table 1).…”
mentioning
confidence: 99%
“…On Chr 11, a LOD score of 3.15 (p=0.0193) was detected at 92.9 cM near marker D11Mit126 using 16, 24, and 32 kHz. Also located near D11Mit126 is the ahl8 QTL identified as Fscn2 (fascin homologue 2, actin-bundling protein, retinal) (Shin et al 2010). Given that ahl8 is associated with a G-to-A transition (G326A, rs26996001) in Fscn2, we sequenced this nucleotide in 129S6 versus CBACa as previously described (Shin et al 2010) and determined that both strains carry the wildtype G326A allele (data not shown).…”
Section: S6 Crossmentioning
confidence: 96%
“…The expression of fascin-2 is limited to the inner ear and retina (1). The loss of function mutations of fascin-2 have been correlated with hearing loss and autosomal dominant retinitis pigmentosa, presumably because of defective actin bundle structures in hair cell stereocillia and photoreceptors (5)(6)(7)(8)(9)(10). Understanding the molecular mechanisms underlying fascin bundling activity and its regulation may provide new avenues to prevent cancer metastasis and to treat patients with hearing and vision loss.…”
mentioning
confidence: 99%
“…Most of the critical fascin residues are positively charged arginine and lysine residues (11). These residues predominantly cluster at two sites, suggesting that these are the two major actin binding sites (ABS1 and ABS2) 5 that cross-link actin filaments through electrostatic interactions. It has been reported that the phosphorylation of Ser 39 by PKC abrogated fascin bundling activity (15).…”
mentioning
confidence: 99%